Faktor-Faktor yang Berhubungan dengan Kejadian Jatuh/Injury pada Lansia di PSTW Budi Mulia IV Jakarta Dan PSTW Melania Tanggerang - Hendrawati Hendrawati; Dewi Fitriani (Jurnal Persada Husada Indonesia, 2015)
The incidence of falls in the elderly can be affected by intrinsic and extrinsic factors (Darmojo, 2004 quoted from Kane, 1994). The data collected from November 2012 to November 2013 at PSTW Budi Mulia IVwith a total of 200 the number of elderly people, shows the incidence of falls/injury as many as 12 people (6%), while in Jakarta Melania PSTW 20 out of 50 elderly people had experienced incidence of falls/injury (40%). The purpose of this study is to determine the Analysis of factors associated with the incidence of falls/ injury in the elderly at PSTW Budi Mulia IV Jakarta and Tangerang PSTW Melania. This study used a descriptive analytic design which analyse the correlation between two variables, as an indicator of how far the contribution of the dependent variable to the presence of independent variable. This design used cross-sectional approach. The results of the bivariate analysis (correlation test) showed that the following variables had a significant association with the incidence of falls/injury in the elderly in PSTW Budi Mulia IV Jakarta disturbances of gait with P = 0.033 OR 2.062 value, the environment variable with the value of P = 0.000 OR 6.463. While in PSTW Melania Tangerang had the environment variable with the value of P=0.001OR 9,000. Variables that have a weak connection to the incident falls in the elderly at PSTW Budi Mulia IV Jakarta is cognitive impairment with P = 0.103, while at PSTW Melania Tangerang, gait disturbance with the value of P = 0.144 OR 2.528 and cognitive impairment with P=0.404.